Community-based seedbanks increase access and availability of high-quality seeds for 189,000 farmers in East Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
CCAFS East Africa and the Alliance of Bioversity International and CIATpartnered with national research institutions to establish community seedbanks for storage and multiplication of diverse, resilient, high-quality seeds adapted to local climatic conditions, reaching 189,000 farmers in East Africa.